Advanced practice providers proficiency‐based model of ultrasound training and practice in the ED. Issue 1 (11th January 2022) - Huang, Calvin; Morone, Christina; Parente, Jason; Taylor, Sabian; Springer, Caitlin; Doyle, Patrick; Temin, Elizabeth; Shokoohi, Hamid; Liteplo, Andrew
Abstract: Competency in the application of point‐of‐care ultrasound (POCUS) has come to be an expected fundamental skill set for advanced practice providers (APPs) in the emergency department. Both American College of Emergency Physicians and the Society of Emergency Medicine Physician Assistants approve of and endorse POCUS use by APPs. However, clinical exposure to and practice of ultrasound in this setting is often variable and without structure. POCUS training must be evolved into a system where developed skills are compatible with clinical need and expectations of APPs. At our institution, we developed a formal, structured POCUS training program for emergency medicine (EM) APPs (including physician assistants and nurse practitioners) and evaluated its efficacy quantitatively by means of a proficiency index. This report examines the EM POCUS training most common to physician assistants and nurse practitioners before practicing at our institution and explores the components of our POCUS training program that have affected program development.